REFORM AND REVIVAL AS ‘REVITALIZATION’: AN APPRAISAL IN THE KERALA MUSLIM CONTEXT - Mujeebu R. Vazhakkunnan (J. S. Asian Stud., 2015)
The most striking feature of the Kerala Muslim landscape is its organizational vitality. Clearly, the sheer plethora of Muslim organizations and the broad range of their activities, all traceable to the reform agendas instituted in the late 19th century, imply demands on the Kerala Muslim public; they also mark an attempt to both interpret and retain the dictates of their faith. The challenge lies essentially in conceptualizing this historical and sociological space, and in what follows we attempt to do precisely this. Following Wallace (1956), this article intends to characterize the reform and revival among Kerala Muslim as a form of revitalization. Hopefully, this will add a further dimension for describing the trajectories of reform and revival in the Kerala Muslim context, and, therefore offers an alternative window into the specificity of Muslims, both in the pan-Indian context and particularly in the specific context of Kerala